Neuronal spiking activity highlights a gradient of epileptogenicity in human tuberous sclerosis lesions. Issue 4 (April 2019) - Despouy, Elodie; Curot, Jonathan; Denuelle, Marie; Deudon, Martin; Sol, Jean-Christophe; Lotterie, Jean-Albert; Reddy, Leila; Nowak, Lionel G.; Pariente, Jérémie; Thorpe, Simon J.; Valton, Luc; Barbeau, Emmanuel J.
Highlights: First recordings of spiking neuronal activity in the tuber and perituberal tissue using new hybrid electrodes equipped with tetrodes. Gradient of epileptogenicity running from the tuber to perituberal tissue revealed by multi-scale analyses. Observation of interactions both within and between the tuber and perituber. Abstract: Objective: The mechanisms underlying epileptogenicity in tuberous sclerosis complex (TSC) are poorly understood. Methods: We analysed neuronal spiking activity (84 neurons), fast ripples (FRs), local field potentials and intracranial electroencephalogram during interictal epileptiform discharges (IEDs) in the tuber and perituber of a patient using novel hybrid electrodes equipped with tetrodes. Results: IEDs were recorded in the tuber and perituber. FRs were recorded only in the tuber and only with the microelectrodes. A larger proportion of neurons in the tuber (57%) than in the perituber (17%) had firing-rates modulated around IEDs. Conclusions: A multi-scale analysis of neuronal activity, FRs and IEDs indicates a gradient of epileptogenicity running from the tuber to the perituber. Significance: We demonstrate, for the first time in vivo, a gradient of epileptogenicity from the tuber to the perituber, which paves the way for future models of epilepsy in TSC. Our results also question the extent of the neurosurgical resection, including or not the perituber, that needs to be made in these patients.